Landscape and niche specialisation of two brush-tailed mice species Calomyscus elburzensis and C. hotsoni in Iran: a case of the role of ecological niche modelling in finding area(s) of contact. Issue 5 (3rd September 2019) - Hamidi, Kordiyeh; Matin, Maryam M.; Kilpatrick, C. William; Eskandarzadeh, Naeimeh
Abstract : Brush-tailed mice (family Calomyscidae) are small rodents found on the Iranian plateau and surrounding areas. To date, little discussion of the ecological aspects, habitat suitability and niche differentiation has been provided for members of this family. Herein, to model the potential distributions and describe habitat preferences of Calomyscus elburzensis and C. hotsoni, the maximum entropy modelling (MaxEnt) approach was used based on data collected through field expeditions, review of the literature and various databases. Species distribution modelling showed that minimal temperature of the coldest month and precipitation of the coldest quarter were the most important factors in predicting the distribution of C. elburzensis . However, occurrence of C. hotsoni was affected greatly by isothermality and annual precipitation. The mountainous regions in northeastern Iran, the central portions of the Elburz Mts, and the eastern hillsides of the Zagros Mts were identified as the most suitable habitats for C. elburzensis, whereas the western parts of South Khorasan province, the forest steppes in the southeast of Iran, and the southwestern extension of the Jebal Barez Mts in central Iran were highly suitable for C. hotsoni . Measurement of ecological niche overlaps showed low similarity between the niches of these two species. Nevertheless, the modelling identified areas of suitable habitat in the north centre parts of both South Khorasan and Kerman provinces where both or either of these species could occur. Moreover, C. elburzensis inhabited cold mountains, Mediterranean, and cold semi-desert climatic conditions, whereas C. hotsoni was generally showed high level of habitat suitability to hot dry desert and hot semi-desert climatic conditions. C. elburzensis mainly inhabits forest steppe and semi-desert biotopes, whereas C. hotsoni occupies desert lowlands in addition to forest steppe and semi-desert biotopes. Further studies are needed to resolve the distribution of each species and to follow their interactions in potential contact zones.